2007
DOI: 10.1002/jcb.21564
|View full text |Cite
|
Sign up to set email alerts
|

Specific LPA receptor subtype mediation of LPA‐induced hypertrophy of cardiac myocytes and involvement of Akt and NFκB signal pathways

Abstract: Lysophosphatidic acid (LPA) is a bioactive phospholipid with diverse functions mediated via G-protein-coupled receptors (GPCRs). In view of the elevated levels of LPA in acute myocardial infarction (MI) patients we have conducted studies aimed at identifying specific LPA receptor subtypes and signaling events that may mediate its actions in hypertrophic remodeling. Experiments were carried out in cultured neonatal rat cardiomyocytes (NRCMs) exposed to LPA and in a rat MI model. In NRCMs, LPA-induced hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 40 publications
1
22
0
1
Order By: Relevance
“…LPA also is linked to NF-κB activation in other cellular phenotypes including fibroblasts [38], endothelial cells [39] and cardiac myocytes [40]. LPA signaling increases Ca 2+ i within MC3T3-E1 osteoblastic cells through either receptor LPA 1 or LPA 3 [36].…”
Section: Resultsmentioning
confidence: 99%
“…LPA also is linked to NF-κB activation in other cellular phenotypes including fibroblasts [38], endothelial cells [39] and cardiac myocytes [40]. LPA signaling increases Ca 2+ i within MC3T3-E1 osteoblastic cells through either receptor LPA 1 or LPA 3 [36].…”
Section: Resultsmentioning
confidence: 99%
“…In response to cardiac damage, the heart often enlarges to compensate for reduced contractile force, in a process known as hypertrophy. Experiments both in vivo and in vitro showed that LPA 1 and LPA 3 contribute to the hypertrophic response through the activation of G i and multiple downstream effectors, including Rho, PI3K/Akt, and NF-kB [33, 34]. …”
Section: Lpa Signaling In Human Diseasementioning
confidence: 99%
“…Among the mitogen-activated protein kinases (MAPKs) superfamily, ERK1/2 has been reported to mediate both adaptive (Gαq mediated) (Bueno et al, 2000) and maladaptive (via Gβγ) (Lorenz et al, 2009) processes through different phosphorylation sites within the heart. As the underlying mechanisms of LPA-induced cardiomyocyte hypertrophy involve activation of Akt and ERK-NFκB (Chen et al, 2008; Yang et al, 2013b), with Gαq-dependent signaling by LPA 3 reported in other cell systems like vascular smooth muscle (Kim et al, 2006), we speculate that in contrast with detrimental effects of ISO-β-AR activation, LPA-LPA 3 signaling might represent another upstream stimulus for adaptive hypertrophy.…”
Section: Discussionmentioning
confidence: 73%
“…LPA induces cardiomyocyte hypertrophy through a mechanism involving both Gi and the small G protein Rho (Hilal-Dandan et al, 2004), which is different from G proteins that ISO-β-AR couples to. After binding to Gi, LPA 3 activates Akt and ERK-NFκB, and then promotes the expression of fetal phenotype gene markers ANP and BNP (Chen et al, 2008; Yang et al, 2013b). These data suggest that β-AR and LPA 3 mediate distinct effectors and, in support of this, the present study provides experimental evidence for LPA-LPA 3 signaling being distinct from ISO-β-AR-mediated myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation